Optimasi Pengendalian Kualitas Produk Usaha Yang Dimiliki Oleh Koperasi Melalui Pendekatan Metode Six Sigma - Anggraeni, Noerlina; Maulana, Arman; Rosmayati, Siti (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The right product and service quality according to consumer preferences plays a crucial role in determining the success of a company. Therefore, a deep understanding of consumers, their needs, and the expectations that must be met is an important aspect for an organization. In order to maximize quality improvement efforts, the Six Sigma method is an inseparable key element. This method has been proven effective in optimizing product and process quality, with a positive impact on reducing defect rates that negatively impact company performance. Through a structured and measurable approach, Six Sigma is able to direct companies towards sustainable development. The Six Sigma method includes a series of steps known as DMAIC, namely Define - Measure - Analyze - Improve and Control. Through the Definition stage, companies identify problems or opportunities for improvement explicitly and map out the project framework. The Measurement step refers to collecting relevant data to analyze the initial situation, while the Analysis stage is used to analyze data in depth to identify the root cause of the problem. After that, the Improvement stage is carried out by designing and testing appropriate solutions to address the identified problems. Finally, the Control step ensures that the changes implemented are maintained and sustained for the long term.